INTELLIGENT FISH FARM IS THE FUTURE OF AQUACULTURE (Scientific journal of the Fergana State University, 2024)
With the constant expansion of the scale and density of aquaculture, modern aquaculture methods have been forced to overproduce products, which has led to an accelerated rate of imbalance in the aquatic environment, the frequent occurrence of fish diseases and a decrease in the quality of aquatic products. Moreover, with the average age of farm workers in many parts of the world being higher, fisheries production will face a labor shortage dilemma and aquaculture practices are in urgent need of change. Modern information technologies have gradually penetrated into various areas of agriculture, and the concept of smart fish farms has also begun to take shape. The intelligent fish farm attempts to carry out the precise work of increasing oxygen, optimizing feeding, reducing disease and precise harvesting, using the idea of ​​"replacing man with machine" to completely free up labor and realize green and sustainable aquaculture. . This article examines the application of smart fishing equipment, the Internet of Things, edge computing, 5G and artificial intelligence algorithms in modern aquaculture, and also analyzes existing problems and prospects for further development. Meanwhile, based on various business requirements, the design framework of key functional modules in building an intelligent fish farm is proposed.